Production of parthenogenetic embryos using chemical activation of oocytes in murine, bovine and caprine species / Siti Khadijah Idris - Siti Khadijah , Idris (2014)
Since the crucial step in successful nuclear transfer protocols is the activation of recipient oocytes, incomplete oocyte activation may result in inability of pronuclear formation which leads to unsuccessful nuclear transfer. Therefore, it is important to establish an optimal method to activate caprine oocytes in order to proceed to the next step of cloning technique. The main aims of this study were to produce and evaluate the embryonic development of parthenogenetic murine, bovine and caprine embryos using various activation chemicals either by single or combination treatments as well as to evaluate the effect of post-hCG duration (in murine) and IVM duration (in caprine) on the subsequent parthenote development. In Experiment 1, the effects of the different combinations of activation chemical on the production of parthenogenetic murine embryos as model animals were studied. Four different groups were compared which are: Group 1 was to evaluate the optimal SrCl2 concentration (2, 4, 6, 8 and 10 mM) + 5 μg/ml CB; Group 2 was to evaluate the optimal duration incubation in 10 mM SrCl2 (1, 2, 3, 4 and 5 hours) + 5 μg/ml CB; Group 3 was to compare the optimal combination agent (6-DMAP, CHX and CB) + 5 μM A23187; and Group 4 was to compare the optimal concentration of EtOH (7, 8 and 9%) + 2 mM 6-DMAP. Generally, the results showed that treatment of murine oocytes in combination of 10 mM SrCl2 + 5 μg/ml CB for 3 hours was significantly (P<0.05) the highest when compared to the optimal treatments from each group. In Experiment 2, even though there was insignificant difference (P>0.05) in the percent of murine oocytes with polar body between two groups of post-hCG duration [70.69±1.04% (13-15 hours) vs. 70.08±1.05% (16-18 hours)], 13-15 hours duration gave significantly (P<0.05) the highest embryonic development at all stages [81.90±1.53% vs. 76.41±1.64% (2-cell); 67.87±2.02% vs. 60.20±1.92% (4-cell); 55.50±2.25% vs. 48.37±1.96% (8-cell); 43.68±2.42% vs. 35.19±2.01% (morula); and 34.36±2.34% vs. 26.04±1.88% (blastocyst), respectively] compared to those of 16-18 hours duration. In Experiment 3, bovine was used as a model species of livestock animals and the effect of different combinations of activation chemical was evaluated. There were five treatments evaluated in this experiment included Treatment 1: A23187 + 6-DMAP; Treatment 2: Iono + 6-DMAP; Treatment 3: EtOH + 6-DMAP; Treatment 4: Iono + CHX; and Treatment 5: IVF control. Generally, there was no significant difference (P>0.05) in all treatments. However, treatment with combination of 10 μM Iono (5 minutes) + 2 mM 6-DMAP (4 hours) gave the highest embryonic cleavage rates compared to the other combination treatments. In Experiment 4, effect of different combinations of activation chemical on the production of parthenogenetic caprine embryos obtained from LOPU procedure was studied. No significant difference (P>0.05) was observed in the comparison of activation by single chemical (Iono vs. A23187). For the activation by combination treatments, four group of combinations were evaluated included Group 1: 5 μM A23187 + 2 mM 6-DMAP (3, 4, 5 and 6 hours); Group 2: 10 μM Iono + 2 mM 6-DMAP (3, 4, 5 and 6 hours); Group 3: 10 μM Iono + 10 μg/ml CHX (3, 4, 5 and 6 hours); and Group 4: 10 μM Iono + 5 μg/ml CB (3, 4, 5 and 6 hours). There were insignificant differences (P>0.05) when comparing the parthenote development from the optimal treatments in each group with IVF control. However, treatment with 10 μM Iono + 2 mM 6-DMAP for 6 hours exhibited the highest cleavage (96.15±3.85%) and blastocyst (35.00±13.72%) rates. Cleavage rates from 8-cell to blastocyst were significantly higher (P<0.05) than IVF control. In Experiment 5, two groups of IVM duration was compared (18-21 vs. 22-25 hours) for LOPU-derived oocytes. At 18-21 hours IVM duration, Grade D oocytes showed significantly lower (P>0.05) in maturation rate compared to Grades A and B oocytes. Similarly, at 22-25 hours IVM duration, the maturation rates of Grades A and B oocytes were significantly higher (P<0.05) than Grade D oocytes. In addition, maturation rate of Grades A and B oocytes from group of 18-21 hours IVM was significantly higher (P<0.05) than Grade D oocytes from 22-25 hours IVM group. No differences (P>0.05) were observed in cleavage and blastocyst rates for all oocyte grades from Group 18-21 hours IVM duration. In contrast, at 22-25 hours IVM duration, cleavage rate of Grade C oocytes was significantly lower (P<0.05) than Grade D oocytes (84.75±4.73% vs. 96.15±3.85%, respectively), whereas blastocyst rate of Grade A oocytes was significantly higher (P<0.05) than Grade D oocytes (23.22±6.36% vs. 7.69±5.21%, respectively). In conclusion, for murine study, combination of 10 mM SrCl2 + 5 μg/ml CB for 3 hours is the optimal way to produce parthenogenetic murine embryos and duration of 13-15 hours post-hCG injection was found to be a better choice to give higher percentage of oocytes with polar body and subsequent parthenote development. As for bovine study, treatment with combination of 10 μM Iono (5 minutes) + 2 mM 6-DMAP (4 hours) was the optimal method to produce parthenogenetic bovine embryos. As for caprine species, combination of 10 μM Iono (5 minutes) + 2 mM 6-DMAP (6 hours) is the optimal protocol to produce parthenogenetic caprine embryos and duration of 18-21 hours IVM is a better choice to give higher percentage in maturation rate and subsequent parthenote development. These findings are useful to be considered in future experiments involving nuclear transfer protocols and other advanced reproductive technologies in mammalian species.